Role of Yapana Basti Along with Gokshuradi Vati in Ksheen Shukra w.s.r. Oligozoospermia - Dutt, Sunil; Dayal, Shambhu; Patel, Falgun (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Shukra is considered as the supreme Dhatu, responsible for normal sexual functioning, both procreation as well as sexual potency to cohabit. Acharya has explained the importance of the ultimate DhatuShukra as above, which is must for life and decrease in its quality or quantity may result into many ailments or even death. Ksheena Shukra is an acquired abnormality of Shukra Dhatu. Qualitative as well as quantitative reduction in Shukra Dhatu occurs in it. Sushruta and Vagabhata have mentioned Ksheena Shukra among the Ashtavidha Shukradushti caused by the vitiation of Vata and Pitta Dosha. Ksheena Shukra may be correlated with Oligozoospermia. Oligozoospermia (decrease and abnormality in sperm count) leads to male infertility. These cases are increasing now a days due to sedentary lifestyle including bad food habits. Material and Method: According to Maharishi Charaka, in management of Ksheena Shukra, Yapana Basti is mentioned. Yapana Basti is said to be Shukravardhaka and works as both Niruha and Anuvasana. Also, it can be given in all seasons. Seeing all these benefits of Yapana Basti, we have selected Yapana Basti along with Gokshuradi Vati. Result and Discussion: It is indicated in Basti-Medhrapaka, Prikartika, Mutrakruchra and in all the disease of Pitta etc. conditions. Considering the direct reference of Vrushyatama Basti it was selected for the present study.